Carbonization, activation and adsorbent properties of a Venezuelan coal - Pérez, María; Guerrero, Clara (Rev. Téc. Fac. Ing. Univ. Zulia)
The activation process of a Venezuelan coal from West Basin. Fila Maestra Sector, Anzoátegui State, Venezuela, was carried out. Also the adsorbent properties of the five best activated coals were investigated. The material was crushed and characterized, followed by carbonization and activation. The studied variables were carbonization time (between 0 and 120 min); carbonization temperature (between 300 and 900°C); activation time (between 0 and 10 h), activation temperature (600 and 900°C); activating agent (water steam and carbon dioxide). The particle size between 1 and 4 mm was utilized, because these sizes are commonly used in industrial processes. The best conditions for carbonization were t= 60 min and T= 600°C and for activation t=2 h and T= 900°C, using water steam as the activating agent. The products were caracterized according to their adsorbent properties and the results obtained indicate that they could be employed in water treatment and possibly for oil treatment.